Design and performance of a manual extruder for recycled plastic-brick composite pavers - Daikh, Abdelkader; Moulai Arbi, Youcef; Bentahar, Mohammed; Mahmoudi, Noureddine (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: This study aimed to develop a cost-effective manual plastic brick extruder for manufacturing composite bricks from recycled polypropylene and brick powder. The goal was to address housing challenges in developing countries while promoting sustainable waste management.Methods: A single screw extruder with a 60 mm die was fabricated, featuring a manual crank, a heating system, and a hopper. Composite specimens with varying polypropylene (30-80 weight percentages) and brick powder (20-70 weight percentages) ratios were produced. Mechanical testing was conducted, including compressive strength, flexural strength, impact resistance, and density measurements.Results: The 40:60 polypropylene:brick powder mixture exhibited optimal compressive strength, ranging from 23.76-24.90 MPa. Flexural strength peaked at the 50:50 ratio (11.86-12.5 MPa). Impact resistance decreased with increasing brick powder content. Density increased linearly with brick powder content, ranging from 1.48-1.77 g/cm³. The extruder successfully produced uniform composite specimens across all mixtures.Conclusions: The study demonstrated the feasibility of producing composite bricks using a low-cost, manually operated extruder. Two optimal mixture compositions were identified: 40:60 polypropylene:brick powder for maximum compressive strength and 50:50 for optimal flexural strength. This approach offers a promising solution for affordable housing construction while addressing plastic waste management in developing regions. Future research should focus on optimizing the extrusion process, exploring additional waste materials, and conducting long-term durability studies of composite bricks.
Keywords: manual extruder; polypropylene; brick powder; composite; pavers